2015
DOI: 10.5199/ijsmart-1791-874x-20d
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Leisure Constraints Model in the Context of Asian International Students

Abstract: The purpose of the current study was to examine the psychometric properties of a leisure constraints model within the context of Asian international students attending colleges in the U.S. Data were collected from a sample of 116 Asian international students attending a Midwestern university in the U.S. Eight (7 constraints and a dependant) factors were identified through EFA with a promax rotation. Construct validity of leisure constraints was confirmed with a CFA . Among the constraint factors, the Lack of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Validity of this instrument was based on 16 constraint questions, which was confirmed by a panel of scholars who have experience working with recreation and intramural sport participants (Author & Author, 2016;Park et al, 2015). Mainly, the insertion of 'intramural sport' was added to questions to narrow the participant's focus to a specific aspect of leisure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Validity of this instrument was based on 16 constraint questions, which was confirmed by a panel of scholars who have experience working with recreation and intramural sport participants (Author & Author, 2016;Park et al, 2015). Mainly, the insertion of 'intramural sport' was added to questions to narrow the participant's focus to a specific aspect of leisure.…”
Section: Discussionmentioning
confidence: 93%
“…However, few studies have compared campus recreation intramural sport program participation rates between domestic and international students to include alternative physical activity opportunities students may participate. Previous studies have utilized the hierarchical model on leisure constraints to examine collegiate students' leisure constraints based on participation in campus recreational sport programs (Guo & Ross, 2014;Park, Yoh, & Park, 2015;. The current study utilizes the hierarchical model of leisure constraints to determine whether significant participation differences exists in competitive activities (non-university affiliated) and intramural sport programs (university affiliated), and which leisure constraints (intrapersonal, interpersonal, and structural) affect participation between domestic and international students.…”
Section: Leisure Constraints Theorymentioning
confidence: 99%
“…Previous studies indicated that international students strongly perceived two constraints to participating in campus recreation services—(a) lack of time due to work, school, or family and (b) lack of information on campus recreation programs (Guo & Ross, 2014). Asian students who experience very high levels of academic pressure spend less time relaxing and socializing (Park et al, 2015). A recent study indicated that beside lack of time, the two most significant factors in preventing participation in campus recreation services among international students were lacking someone to work out with and being unaware of the recreation facilities (Nandini, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In that study, 23% of 155 total subjects were graduate students but no differences were explored between graduate and undergraduate students. Several previous studies (e.g., Milton & Patton, 2011; Nandini, 2017; Park et al, 2015) included international graduate students, but none of those studies examined graduate and undergraduate students separately.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation